Inferring and Explaining - Johnson, Jeffery L. (Open textbook library., 2019)
Inferring and Explaining is a book in practical epistemology. It examines the notion of evidence and assumes that good evidence is the essence of rational thinking. Evidence is the cornerstone of the natural, social, and behavioral sciences. But it is equally central to almost all academic pursuits and, perhaps most importantly, to the basic need to live an intelligent and reflective life. The book further assumes that a particular model of evidence— Inference to the Best Explanation—not only captures the essence of (good) evidence but suggests a very practical, and pedagogically useful, procedure for evidence evaluation. The book is intended primarily for two sorts of introductory courses. First and foremost are courses in critical thinking (or informal or practical logic). In addition, however, the book has application in more general courses (or major sections of courses) in introductory philosophy.